EVOLUTIONARY ALGORITHM FOR THE PROBLEM minimum spanning tree (MST) - Mayta H., Rosmeri (2002)
The MST has a venerable history in combinatorial optimization. It was initially developed in 1926 by Boruvka who says he had to learn for the electrification of southern Moraria where he provided a solution to find the most economical distribution through a network of a power line.